Hematologic and biochemical reference intervals for captive Asian elephants (Elephas maximus) in Thailand - Thittaya Janyamethakul (2018)
© 2017, Veteriner Fakultesi Dergisi. All rights reserved. Species specific blood value reference intervals are needed for the proper diagnosis, and treatment of disease, appropriate for specific populations, because age, sex, management, exercise and geographical location can all affect hematological values. The aim of this study was to establish a set of hematology and blood chemistry reference intervals for captive Asian elephants. Blood samples were collected from 149 healthy Asian elephants in 15 tourist camps in Northern Thailand. Hematological and biochemical parameters were determined. The results showed similarity of haematological and blood chemistry range to others previously published. There were no sex differences for most hematological parameters except some parameters were different i.e. MCV, MCHC, BUN, AST, and ALP. The hematology and blood chemistry reference intervals of our study can be used as the reference for hematological analysis in Thailand, and several Asian elephant range countries and zoos.